2014
DOI: 10.1093/molbev/msu295
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics Reveals Chromosome-Scale Heterogeneous Evolution in a Protoploid Yeast

Abstract: Yeast species represent an ideal model system for population genomic studies but large-scale polymorphism surveys have only been reported for species of the Saccharomyces genus so far. Hence, little is known about intraspecific diversity and evolution in yeast. To obtain a new insight into the evolutionary forces shaping natural populations, we sequenced the genomes of an expansive worldwide collection of isolates from a species distantly related to Saccharomyces cerevisiae: Lachancea kluyveri (formerly S. klu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(114 citation statements)
references
References 45 publications
5
106
3
Order By: Relevance
“…We confirmed that the orthologs of LIF1 and NEJ1 were missing from the L. kluyveri reference genome (Fig. 2) and from the 28 sequenced strains of L. kluyveri (Friedrich et al 2015). A relic of NEJ1 was found next to a rearrangement breakpoint in the L. kluyveri genome, suggesting that the loss of NEJ1 resulted from a gene disruption event (Supplemental Fig.…”
Section: −30supporting
confidence: 71%
See 3 more Smart Citations
“…We confirmed that the orthologs of LIF1 and NEJ1 were missing from the L. kluyveri reference genome (Fig. 2) and from the 28 sequenced strains of L. kluyveri (Friedrich et al 2015). A relic of NEJ1 was found next to a rearrangement breakpoint in the L. kluyveri genome, suggesting that the loss of NEJ1 resulted from a gene disruption event (Supplemental Fig.…”
Section: −30supporting
confidence: 71%
“…In L. kluyveri, a region of 1 Mb containing the MAT locus and covering almost the whole left arm of chromosome C, has an average GC content of 52.9%, which is significantly higher than the 40.4% global GC content of the rest of the genome (Payen et al 2009;Souciet et al 2009). The orthologous counterpart of this chromosomal region is found in all other Lachancea species, but none of them presented the GC content heterogeneity characterized in L. kluyveri, reinforcing the hypothesis of an introgression event at the origin of this chromosomal arm (Friedrich et al 2015).…”
Section: High-quality Reference Genomes Of the Lachancea Genusmentioning
confidence: 60%
See 2 more Smart Citations
“…Subsequent technological advances made it possible to sequence other fungal genomes [2][3][4][5][6]. This in turn allowed researchers to compare the genomes of different yeast species, investigate the specific order of genes and study the organization and evolution of biological pathways and regulatory modules [7,8].…”
Section: Introductionmentioning
confidence: 99%